Improving the Gas‐Separation Properties of PVAc‐Zeolite 4A Mixed‐Matrix Membranes through Nano‐Sizing and Silanation of the Zeolite. Issue 12 (7th June 2019) - Esmaeili, Nazila; Boyd, Sue E.; Brown, Christopher L.; Mac A. Gray, Evan; Webb, Colin J.
Abstract: Mixed‐matrix membranes containing synthesised nano‐sized zeolite 4A and PVAc were fabricated to investigate the effect of zeolite loading on membrane morphology, polymer‐filler interaction, thermal stability and gas separation properties. SEM studies revealed that, although the membranes with 40 wt % nano‐sized zeolite particles were distributed uniformly through the polymer matrix without voids, the membranes with 15 wt % zeolite loading showed agglomeration. With increasing zeolite content, the thermal stability improved, the permeability decreased and the selectivity increased. The effect of silanation on dispersion of 15 wt % zeolite 4A nanoparticles through PVAc was investigated by post‐synthesis modification of the zeolite with 3‐Aminopropyl(diethoxy)methylsilane. Modification of the nanoparticles improved their dispersion in PVAc, resulting in higher thermal stability than the corresponding unmodified zeolite membrane. Modification also decreased the rigidity of the membrane. Partial pore blockage of the modified zeolite nanoparticles after silanation caused a further decrease in permeability, compared to the 15 wt % unmodified zeolite membrane. Abstract : Nano‐sized zeolite for mixed matrix membranes : Pure‐gas‐permeation measurements on PVAc mixed‐matrix membranes with nano‐particular zeolite as the inorganic filler demonstrate the advantages of nano‐sizing the zeolite for gas‐separation applications. At low filler content levels, agglomeration of the nanoparticles is avoided by silanation of the zeolite before incorporation into the polymer.